2019
DOI: 10.33151/ajp.16.729
|View full text |Cite
|
Sign up to set email alerts
|

National Study of Saudi Arabian Emergency Medical Services Professional Profiles: An Inferential Analysis

Abstract: IntroductionInternationally, emergency medical services (EMS) are an essential access point to the healthcare system. Building an understanding of the professional, educational and demographic profiles of an EMS workforce is important. The aim of this study is to statistically test the professional profiles of EMS providers against the Saudi ParamEdic Competency Scale (SPECS) model factors.MethodsHealthcare providers working for the Saudi Red Crescent Authority (SRCA) were surveyed using a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A national study of EMS professionals in Saudi Arabia found that there were considerably more Diploma and lower quali cations than Bachelor, Masters or PhD [18]. However, the participants in the current study believed that there was a difference between urban and rural areas in this area.…”
Section: Composition Of the Workforcementioning
confidence: 53%
See 1 more Smart Citation
“…A national study of EMS professionals in Saudi Arabia found that there were considerably more Diploma and lower quali cations than Bachelor, Masters or PhD [18]. However, the participants in the current study believed that there was a difference between urban and rural areas in this area.…”
Section: Composition Of the Workforcementioning
confidence: 53%
“…Interviewees were determined on the basis of rst-respondents, and the interviews continued until data saturation was reached. It was known in advance that it was highly likely that all participants would be male, as this is re ective of the demographic makeup of the Saudi Red Crescent EMS workforce [17,18].…”
Section: Study Setting and Participantsmentioning
confidence: 99%
“… 31 According to nurses in this study, there were two main points that could enhance the effectiveness of triage implementation in emergency unit of public health care centers: patient honesty and selective selection. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…The EMS in Saudi Arabia is provided by the Saudi Red Crescent Authority (SRCA). It was established in 1934 and combined more than 5,000 male emergency medical technicians (EMT) and paramedics around the country (Alshammari et al , 2019; Saudi Red Crescent Authority, 2019). Despite change within the Kingdom, the prehospital field represents an imbalanced gender proportion, with less than 10% of women in the total paramedic workforce than those working inside hospitals (Alharthy et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi society, which is considered to be conservative, female patients reportedly prefer female paramedics to care for them due to privacy and cultural sensitivities, suggesting the Saudi EMS needs to employ female paramedics in the Saudi workforce (Alshammari et al , 2019; Alharthy et al , 2018). Due to the conservative Saudi culture, Hamam et al (2015) investigated the acceptability of care providers by Saudi female patients.…”
Section: Introductionmentioning
confidence: 99%